HUMIC ACID AND INDOLE ACETIC ACID AFFECT YIELD AND ESSENTIAL OIL OF DILL GROWN UNDER TWO DIFFERENT LOCATIONS IN EGYPT - Hah, Said-al Ahl; Ag, El Gendy; Ea, Omer (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of this work was to evaluate the effect of humic acid, indole acetic acid or combination on productivity, essential oil of dill plant cultivated in two different locations. Also, to study the dill straw as a new source of essential oil instead of neglecting this by-product. Methods: In 2010/2011 and 2011/2012, a field experiment was conducted in Egypt to evaluate the effect of humic acid (0 and 400 ppm), indole acetic acid (0 and 400 ppm) and region (Nile Valley and Delta, Giza governorate and Sinai Peninsula, North Sinai governorate) on dill productivity, oil content and its composition. Results: Results demonstrated that dill straw can be explored as a new source of essential oil. Generally found that the cultivation of dill in Giza gave the best results from cultivation in the North Sinai. For spraying treatments, there was a disparity in the response studied characters, where spraying by humic acid gave the best results of survival %, plant height, number of branches, number of umbles and seed oil yield (l/fed). While the best values of dill straw (g/plant or kg/fed) and the percentage of oil seed were obtained with indole acetic acid spray. Also, indole acetic acid+humic acid gave the best values of seed weight (g/plant or kg/fed) and straw volatile oil content (% or l/fed). But, non-spraying plants gave lower values of all studied characters. As for interaction treatments, spraying by humic acid gave the best results of plant height, number of branches and number of umbles in both regions and seed oil (% or yield) at Giza as well as straw oil yield at North Sinai. At the same time, indole acetic acid gave the highest straw (g/plant or kg/fed) and seeds oil % at North Sinai. But, indole acetic acid+humic acid gave the highest seeds (g/plant or kg/fed) and straw oil in regions as well as seeds and straw oil yields in North Sinai and Giza, respectively. Overall, indole acetic acid under the conditions of the Giza region gave the best results for straw (g/plant or kg/fed), while spray with humic acid gave the highest values of plant height, number of branches, number of umbles and seed volatile oil (% or yield) in Giza as well as the highest of seed weight (g/plant or kg/fed) and straw volatile oil (% or yield) was obtained by indole acetic acid+humic acid. In view of the components of the volatile oil found that carvone, dihydrocarvone, limonene, dill apiol and piperitone compounds in the seed and Î±-phellandrene, limonene, Î²-phellandrene, p-cymene and dill ether compounds in straw was the main compounds. The percentages of these compounds affected by factors under study. Conclusion: Cultivation of dill in Giza region gave the best results from cultivation in the North Sinai region. Humic acid and indole acetic acid play an important role in plant growth, yield and ameliorate the deleterious effects of salt stress. The content of carvone, dihydrocarvone, limonene, dill apiol and piperitone in the seed oil as major compounds and Î±-phellandrene, limonene, Î²-phellandrene, p-cymene, dill ether as major compounds in the straw oil affected by factors under study. Dill straw can be explored as a new source of essential oil.